2018
DOI: 10.4103/jmas.jmas_38_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-port and conventional laparoscopic abdominoperineal resection

Abstract: Background:Within the last two decades, surgical treatment of colorectal cancer has changed dramatically from large abdominal incisions to minimal access surgery. In the recent years, single port (SP) surgery has spawned from conventional laparoscopic surgery. The purpose of this study was to compare conventional with SP laparoscopic abdominoperineal resection (LAPR) for rectal cancer.Patients and Methods:This was a single-center non-randomised retrospective comparative study of prospectively collected data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…This study also contained seven English articles and two Chinese articles. All patients who underwent SILS or CLS were confirmed pathologically for sigmoid colon or rectal cancer [ 9 – 17 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study also contained seven English articles and two Chinese articles. All patients who underwent SILS or CLS were confirmed pathologically for sigmoid colon or rectal cancer [ 9 – 17 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one duplicate not detected by the citation manager was also excluded. Thus, we reviewed the full text of 14 articles (Table I) [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Two studies by Sirikurnpiboon [11,12] had overlapping study populations, and only the most recent study was included for analysis.…”
Section: Article Search Resultsmentioning
confidence: 99%
“…Finally, 3 Korean studies [21][22][23] shared the same population and included sigmoid and rectosigmoid colon cancer, and thus all 3 were excluded. After exclusions, 6 eligible studies remained for meta-analysis [11,13,14,16,17,24]. A flow diagram of the article selection is provided in Figure 1.…”
Section: Article Search Resultsmentioning
confidence: 99%
“…Finally, five studies were eligible in this review, which included one randomized trial and four comparative studies. All patients who underwent SPS or MPS were confirmed pathologically for rectal cancer (7)(8)(9)(10)(11). The flowchart of the selection process for studies included in this review is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The operative time, blood loss and the conversion rate to open surgery were described in five studies. Levic and Bulu (9) and Nerup et al (10) reported that the operative time was significantly longer in the SPS group than in the MPS group (295 min vs. 248 min, P=0.01 and 316 min vs. 269 min, P=0.004, respectively). Sourrouille et al (11) and Levic and Bulu (9) reported that blood loss was significantly less in the SPS group than in the MPS group (100 ml vs. 200 ml, P=0.01 and 35 ml vs. 100 ml, P=0.006, respectively).…”
Section: Patient Profiles Operative Details and Postoperative Outcomesmentioning
confidence: 99%